The study centre of the german surgical society: current trials and results - Knebel, Phillip; Kühn, Shafreena; Ulrich, Alexis; Büchler, Markus W.; Diener, Markus K. (Langenbeck's archives of surgery, 2012)
PurposeThis article provides an overview of current and completed multicentre trials and systematic reviews performed by the Study Centre of the German Surgical Society (SDGC).BackgroundThe SDGC aims to transfer the concept of evidence-based medicine to surgery by planning, conducting and analyzing large national and international randomized multicentre trials concerning surgical issues. Every German surgeon may ask the SDGC for support to realize his clinical trial ideas. Another important task of the SDGC is the acquisition of trial funding from government institutions or industrial partners.DiscussionFive multicentre randomized controlled trials (RCT) and 11 systematic reviews with meta-analyses have already been completed and published by the SDGC. Another seven RCTs are currently in the recruitment or follow up phase. A total of 2,500 patients in over 100 trial centres have participated so far.
Gesehen am 30.10.2018